Multicentre trial evaluating alveolar NO fraction as a marker of asthma control and severity - Mahut, B; Trinquart, L; Le Bourgeois, M; Becquemin, M.-H; Beydon, N; Aubourg, F; Jala, M; Bidaud-Chevalier, B; Dinh-Xuan, A.-T; Randrianarivelo, O; Denjean, A; de Blic, J; et al. (Allergy (Copenhagen), 2010)
To cite this article: Mahut B, Trinquart L, Le Bourgeois M, Becquemin M-H, Beydon N, Aubourg F, Jala M, Bidaud-Chevalier B, Dinh-Xuan A-T, Randrianarivelo O, Denjean A, de Blic J, Delclaux C. Multicentre trial evaluating alveolar NO fraction as a marker of asthma control and severity. Allergy 2010; 65: 636-644. Exhaled NO can be partitioned in its bronchial and alveolar sources, and the latter may increase in the presence of recent asthmatic symptoms and in refractory asthma. The aim of this multicentre prospective study was to assess whether alveolar NO fraction and FENO could be associated with the level of asthma control and severity both at the time of measurement and in the subsequent 3 months. Asthma patients older than 10 years, nonsmokers, without recent exacerbation and under regular treatment, underwent exhaled NO measurement at multiple constant flows allowing its partition in alveolar (with correction for back-diffusion) and bronchial origins based on a two-compartment model of NO exchange; exhaled NO fraction at 50 ml/s (FENO,₀.₀₅) was also recorded. On inclusion, severity was assessed using the four Global initiative for asthma (GINA) classes and control using Asthma Control Questionnaire (ACQ). Participants were followed-up for 12 weeks, control being assessed by short-ACQ on 1st, 4th, 8th and 12th week. Two-hundred patients [107 children and 93 adults, median age (25th; 75th percentile) 16 years (12; 38)], 165 receiving inhaled corticosteroid, were included in five centres. The two-compartment model was valid in 175/200 patients (87.5%). Alveolar NO and FENO,₀.₀₅ did not correlate to control on inclusion or follow-up (either with ACQ /short-ACQ values or their changes), nor was influenced by severity classes. Alveolar NO negatively correlated to MEF₂₅₋₇₅% (rho = -0.22, P < 0.01). Alveolar and exhaled NO fractions are not indexes of control or severity in asthmatic children and adults under treatment.